Comparative sensitivity of Crassostrea angulata and Crassostrea gigas embryo-larval development to As under varying salinity and temperature. (September 2018) - Moreira, Anthony; Figueira, Etelvina; Libralato, Giovanni; Soares, Amadeu M.V.M.; Guida, Marco; Freitas, Rosa
Abstract: Oysters are a diverse group of marine bivalves that inhabit coastal systems of the world's oceans, providing a variety of ecosystem services, and represent a major socioeconomic resource. However, oyster reefs have become inevitably impacted from habitat destruction, overfishing, pollution and disease outbreaks that have pushed these structures to the break of extinction. In addition, the increased frequency of climate change related events promise to further challenge oyster species survival worldwide. Oysters' early embryonic development is likely the most vulnerable stage to climate change related stressors (e.g. salinity and temperature shifts) as well as to pollutants (e.g. arsenic), and therefore can represent the most important bottleneck that define populations' survival in a changing environment. In light of this, the present study aimed to assess two important oyster species, Crassostrea angulata and Crassostrea gigas embryo-larval development, under combinations of salinity (20, 26 and 33), temperature (20, 24 and 28 °C) and arsenic (As) exposure (0, 30, 60, 120, 240, 480, 960 and 1920 μg. As L −1 ), to infer on different oyster species capacity to cope with these environmental stressors under the eminent threat of climate change and increase of pollution worldwide. Results showed differences in each species range of salinity and temperature for successful embryonic development. For C angulata, embryo-larval development was successful at a narrower range of both salinity and temperature, compared to C. gigas. Overall, As induced higher toxicity to C. angulata embryos, with calculated EC50 values at least an order of magnitude lower than those calculated for C. gigas . The toxicity of As (measured as median effective concentration, EC50) showed to be influenced by both salinity and temperature in both species. Nonetheless, salinity had a greater influence on embryos' sensitivity to As. This pattern was mostly noticed for C. gigas, with lower salinity inducing higher sensitivity to As. Results were discussed considering the existing literature and suggest that C. angulata populations are likely to become more vulnerable under near future predictions for temperature rise, salinity shifts and pollution. Highlights: Thermohaline range for embryo-larval development was wider in C. gigas . C. angulata embryo development was more sensitive to As. As induced a delayed but not permanent effect on embryo development. Salinity and temperature influenced both species sensitivity to As. C. angulata may become most impacted by climate change and pollution than C. gigas .